Preinduction cervical ripening with intravaginal prostaglandin E1 methyl analogue misoprostol: a randomized controlled trial - Srisomboon J. (2014)
To evaluate the efficacy of intravaginal prostaglandin E1 methyl analogue misoprostol in cervical ripening in patients with unfavorable cervix (Bishop score < 4) requiring labor induction.